Pathogen genomics study of an early medieval community in Germany reveals extensive co-infections - Joanna H. Bonczarowska; Julian Susat; Barbara Mühlemann; Isabelle Jasch-Boley; Sebastian Brather; Benjamin Höke; Susanne Brather-Walter; Valerie Schoenenberg; Jonathan Scheschkewitz; Gabriele Graenert; Dirk Krausse; Michael Francken; et al. (Genome Biology, 2022)
Abstract Background The pathogen landscape in the Early European Middle Ages remains largely unexplored. Here, we perform a systematic pathogen screening of the rural community Lauchheim “Mittelhofen,” in present-day Germany, dated to the Merovingian period, between fifth and eighth century CE. Skeletal remains of individuals were subjected to an ancient DNA metagenomic analysis. Genomes of the detected pathogens were reconstructed and analyzed phylogenetically. Results Over 30% of the individuals exhibit molecular signs of infection with hepatitis B virus (HBV), parvovirus B19, variola virus (VARV), and Mycobacterium leprae. Seven double and one triple infection were detected. We reconstructed four HBV genomes and one genome each of B19, VARV, and M. leprae. All HBV genomes are of genotype D4 which is rare in Europe today. The VARV strain exhibits a unique pattern of gene loss indicating that viruses with different gene compositions were circulating in the Early Middle Ages. The M. leprae strain clustered in branch 3 together with the oldest to-date genome from the UK. Conclusions The high burden of infectious disease, together with osteological markers of physiological stress, reflect a poor health status of the community. This could have been an indirect result of the climate decline in Europe at the time, caused by the Late Antique Little Ice Age (LALIA). Our findings suggest that LALIA may have created an ecological context in which persistent outbreaks set the stage for major epidemics of severe diseases such as leprosy and smallpox hundreds of years later.